Wearable Sports Technology Development in Costa Rica: Inertial Measurement Unit Integration for Real-Time External Load Monitoring - Chavarría-Fernández, Victor (2023)
The increasing trend and projection for the use of wearable sensors technology in the general population have led to the development of different inertial measurement units (IMU) to monitor activity and motion variables during exercise or sports. This study aims to systematize the practical experience of developing an inertial measurement device to quantify external load in real time for runners. This article shows the installed capacity of Costa Rican higher education institutions to integrate existing sensors available in the international market in a single device to program it and use it for different sport science purposes. Two scientific laboratories joined resources and integrated an interdisciplinary team composed of exercise physiologists, sports scientists, physiotherapists, and electromechanical engineers who globally faced the challenge of creating SafeRun IMU. In this case, an IMU was constructed with great success, capable of quantifying external load variables controlled from a mobile device in real-time. The results showed an acceptable agreement and reliability of the data extracted from the IMU. The information collected from this IMU could be used to control and quantify external load to develop or redirect exercise programming and prescription and prevent overuse injuries or physical overload conditions. This device differs from other existing ones due to its small size and portability, which benefits its commercialization and massification.